ANALISIS DAYA SAING KOMODITAS KELAPA DI KABUPATEN FLORES TIMUR - Krisna Setiawan (Partner, 2016)
Cultivation of coconut plantations in East Flores has been carried out for generations in which the application of the technical aspects of coconut farming inadequate, irregular plant spacing and fertilizer pickup. But seen from the planting area and production of coconut people it produces, this commodity still has the potential to be developed that are expected to have high competitiveness. This study aims to analyze the profitability of financial and economic, as well as competitive and comparative advantage in coconut in East Flores. The method used as an indicator in analyzing competitiveness is descriptive method by using the Policy Analysis Matrix (PAM). The results showed (1) coconut farm in East Flores has competitive advantages seen from the PP positive and PCR value smaller than one. Additionally it has a comparative advantage seen from the SP positive and DRCR smaller than one; (2) Commodities coconut in East Flores competitiveness is very high and need to be prioritized to be developed, such as by increasing the added value of oil processing.Keywords: Coconut, PAM, comparative advantage, competitive advantage